The calculation and the analysis of the quantity of the total solar radiation incident on tilted surface on a high region above sea level (Latakia University Journal -Basic Sciences Series, 2019)
In this study, special mathematical methods are used to calculate the quantity of the total solar radiation incident on tilted surface on a high area, which is 800m above sea level by means of a computer. This study can be applied for the unit area on any area in Syria or on other areas around the world if the special co-ordinates are known. This is done in order to use the photovoltaic panels to produce electrical energy required to provide energy to the whole loaded needed. The study showed that the total solar radiation quantity was rating between. In addition, the time of the solar radiance measured in hours is rating between  hours. It is also noticed that the total solar radiation almost consists of the direct solar radiation. Moreover, a comparison of these quantities and the quantities recorded on other studies was done on different places around the world and we found that they were the same.